Kinetics of Enzymatic Synthesis - Rajendran, Lakshmanan; Fernandez, Carlos (IntechOpen, 2019)
Kinetics of Enzymatic Synthesis gives insight into different aspects of chemical reactions that are catalyzed by enzymes. This book is divided into two sections: "Enzyme Kinetics" and "Enzymatic Synthesis". The first section consists of two chapters with a halophilic enzyme kinetics and thermodynamic approach towards analyzing the influence of co-solvents on the Michaelis constants of enzyme-catalyzed reactions. The second section consists of three chapters. Production of isoamyl acetate using the enzymatic synthesis method between acetic anhydride and isoamyl alcohol by having enzyme Candida antarctica Lipase B as catalyst in a solvent-free system is discussed in the third chapter. The integrated scheme with the use of the filtrate from the pretreatment of the CS and the growth conditions of Pleurotus cystidiosus is studied in the fourth chapter. The last chapter of this section provides the conditions of the key parameters in microfluidic systems (residence times, flow rates, concentrations) applied for a sequential process from liquid/liquid extraction of LVV-h7.